2020
DOI: 10.1126/science.aaz4797
|View full text |Cite
|
Sign up to set email alerts
|

Demographic trade-offs predict tropical forest dynamics

Abstract: Understanding tropical forest dynamics and planning for their sustainable management require efficient, yet accurate, predictions of the joint dynamics of hundreds of tree species. With increasing information on tropical tree life histories, our predictive understanding is no longer limited by species data but by the ability of existing models to make use of it. Using a demographic forest model, we show that the basal area and compositional changes during forest succession in a neotropical forest can be accura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
173
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(179 citation statements)
references
References 39 publications
3
173
3
Order By: Relevance
“…The importance of big trees, (typically defined as cm diameter-at-breast height, DBH), is widely-recognised in terms of carbon storage, demographics and impact on their surrounding ecosystems 11 14 . Unfortunately the importance of big trees is in direct proportion to the difficulty of measuring them, particularly for AGB.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of big trees, (typically defined as cm diameter-at-breast height, DBH), is widely-recognised in terms of carbon storage, demographics and impact on their surrounding ecosystems 11 14 . Unfortunately the importance of big trees is in direct proportion to the difficulty of measuring them, particularly for AGB.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of these four drivers can represent the growth–survival trade‐off (e.g., the ratio of mortality over radial growth μG appearing in Equation 12) and the stature–recruitment trade‐off (which distinguishes long‐lived pioneers from short‐lived breeders). These two trade‐offs are important for understanding forest dynamics (Rüger et al., 2020, for tropical forest).…”
Section: Discussionmentioning
confidence: 99%
“…1A). Recent work has suggested that tree functional composition change over succession, in terms of differentiation on growth–survival and stature–recruitment tradeoffs, can explain forest structural change, highlighting the likely importance of community and demographic dynamics in forest transitions (Rüger et al 2020). Furthermore, understanding the specific long‐term impacts of forest disturbances on demographic components, recruitment, growth, and mortality is increasingly recognized as central to predicting climate forcing (McDowell et al 2020).…”
Section: Section 1: Reframing Tropical Forest Savannization As Transimentioning
confidence: 99%
“…In this case, the feedback results from regional alterations of temperature and precipitation, which impacts the forest via its sensitivity to variations in these factors. Other factors influencing forest sensitivity and resilience to disturbance such as forest functional composition (Brum et al 2019, Rüger et al 2020) would also play a critical role.…”
Section: Section 3: Reframing Tropical Forest Savannization Challengmentioning
confidence: 99%